Re: Sundblad B-M, Sahlander K, Ek A, Kumlin M, Olsson M, Larsson K, Palmberg L. Effect of respirators equipped with particle or particle-and-gas filters during exposure in a pig confinement building. Scand J Work Environ Health 2006;32(2):145–153. - Sundblad, Britt-Marie; Sahlander, Karin; Ek, Alexandra; Kumlin, Maria; Olsson, Marianne; Larsson, Kjell; Palmberg, Lena (Scandinavian Journal of Work, Environment & Health, 2007)
Table 2 on page 149 of the above-mentioned article was missconstructed. The correct form follows. The editors apologize for the error.
Keywords: airway inflammation; amendment and correction; bronchial responsiveness; exposure; gases; particle filter; particle-and-gas filter; pig confinement building; respirator